The Role of Social Support in Improving the Well-Being of the Elderly: A Qualitative Review - Rubianti, Rubianti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to explore the role of social support in improving the well-being of the elderly through a qualitative review. Social support is identified as a crucial factor influencing the quality of life and happiness of older people in social, emotional and instrumental contexts. Qualitative research methods were used to gain in-depth understanding through in-depth interviews with elderly people and content analysis of related literature. The research results show that family, peers, and community play an important role in providing social support to the elderly. This support not only improves their emotional well-being but also provides practical help in living their daily lives. Seniors who feel strong social support tend to have lower levels of depression, better physical health, and a higher quality of life. Policy suggestions include increasing public awareness about the importance of social support for the elderly, developing community programs that support their social interactions, as well as integrating the concept of social support in public policies related to the welfare of the elderly. It is hoped that this research can make a significant contribution in increasing understanding and approaches to the important role of social support in advancing the welfare of the elderly in society.